Trilogi Kecerdasan dan Kaitannya dengan wahyu (Analisis Tentang Potensi IQ, EQ, dan SQ - Abdul Pandi; Muhammad Amri; Mahmuddin (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research is entirely in the nature of library research. Data collected through library research consisting of source data (primary) in the form of books relating to critical studies of Islamic thought. Data processing is entirely "qualitative", because the data encountered is descriptive in the form of verbal statements. As for the method of analysis using "inductive", deductive" and comparative techniques". The results of this study indicate that. IQ, EQ, and SQ, are brain-centered human intelligence forces that have different orientations and functions, but all three can work well together. IQ that is centered on the left brain gives birth to rational or logical intelligence. EQ or Emotional intelligence is centered on the right brain which gives birth to ethical intuitive emotional intelligence. SQ is centered on the network between the two giving birth to a unitive and transcendent spiritual, with this power humans can find meaning behind all the life experiences that have been lived. IQ, EQ, and SQ, based on the view of the Koran, humans have various psychological potentials and these potentials determine human quality. These potentials are spirit, aql, qalb, and nafs. By modern findings these potentials are then translated into IQ, EQ, and SQ. The potentials given by Allah SWT make it possible to bring people who are desired by Allah SWT to worship Allah or become perfect human beings and or vice versa become humans who are disobedient to Allah SWT.